National pride in news media among youth - Tamam, Ezhar; Wok, Saodah; Bolong, Jusang (Penerbit Universiti Kebangsaan Malaysia, 2011)
National pride among youth could be instilled through dissemination of positive national stories and symbols through the news media. This argument is based on the premise that news media, as 'the fourth state,' is a potent agent of development and can function as nation builder. Much have been discussed and studied about the influence of mass media with most studies conducted in the West, thus, there are a few studies conducted in Malaysia. However, there exists an important gap in the literature on the relationship of exposure and attention to news of public and national affairs with national pride, and whether the relationships vary with ethnicity. This chapter describes the theoretical rational and reports the research design and findings of a national survey designed to examine the relationships of exposure and attention to national and public affairs news in television and newspaper among fifteen to twenty five years old Malay, Chinese and Indian youths in Malaysia.